2015
DOI: 10.1515/jos-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Dwelling Price Ranking versus Socioeconomic Clustering: Possibility of Imputation

Abstract: In order to characterize the socioeconomic profile of various geographic units, it is common practice to use aggregated indices. However, the process of calculating such indices requires a wide variety of variables from various data sources available concurrently. Using a number of administrative databases for 2001 and 2003, this study examines the question of whether dwelling prices in a given locality can serve as a proxy for its socioeconomic level. Based on statistical and geographic criteria, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
2
3
0
Order By: Relevance
“…As expected, the analysis showed that the dwelling area variable explained most of the variance of the dependent variable (Ln price per square metre), consistent with the findings of previous research (Fleishman and Gubman 2015 ). Regarding the effect of the year of construction of a residential building on property value, the model showed an upward trend in the regression coefficients over the years.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, the analysis showed that the dwelling area variable explained most of the variance of the dependent variable (Ln price per square metre), consistent with the findings of previous research (Fleishman and Gubman 2015 ). Regarding the effect of the year of construction of a residential building on property value, the model showed an upward trend in the regression coefficients over the years.…”
Section: Resultssupporting
confidence: 90%
“…UK, Australia, New Zealand) to use aggregated indices with the purpose of characterizing and documenting the socioeconomic profile of various geographical units (Burck and Tsibel 2013 ). The positive effect of socioeconomic profile of CT on property value (Table 3 ) reflects the well-known correlation between property prices and various effects reflecting the socioeconomic characteristics of the population in a given area (Des Rosiers et al 2002 ; Reed 2013 ; Fleishamn et al 2015 ).…”
Section: Resultsmentioning
confidence: 94%
“…Locality size (in terms of number of residents) has a positive effect on housing prices, as expected. These findings are in line with the results reported in other studies recently conducted in Israel (Fleishman and Gubman, 2015a,b). In addition, a significant negative relation is observed between the percentages of households with children aged 4-12 among the homebuyers and the average house price per square meter.…”
Section: Case Study About Quality Schools and Housing Prices: The Case Of Israelsupporting
confidence: 93%
“…Similar to variables reflected socioeconomic characteristics of students and their parents, it should be noted that Israelis generally, and Israeli immigrants specifically, display a wide spectrum of ethnic patterns that are of a great importance not only in the socioeconomic divide in Israeli society, but also in spatial segregation. Moreover, recent study conducted in Israel by Fleishman and Gubman (2015a) shows that the percentage of adult immigrants from Asian and African countries as well as from the former USSR, among neighborhood’s residents, is negatively correlated with housing prices. According to this evidence and following the relevant literature that has been referred in Section 2.2, such characteristics as parents’ origin and education level are expected to influence house prices and are thus included in the models.…”
Section: Case Study About Quality Schools and Housing Prices: The Case Of Israelmentioning
confidence: 99%
See 1 more Smart Citation